Algbra
posted by Zach .
How do you solve this problem?
3/5k  (k + 1/3) = 1/15 (k + 3)
Please show me the steps. Thanks.

I am not a fan of fractions in equations, so I usually multiply each term by the LCD, in this case 15
9k  15(k+1/3) = k+3
9k  15k  5 = k + 3
7k = 8
k = 8/7 
3/5k  (k + 1/3) = 1/15 (k + 3)
remove ( )
3/5k  k  1/3 = 1/15k + 3/15
get rid of denominators
since 15 is the LCD of 5, 3, 15
multiplying both sides by 15 will do this
15 (3/5k  k  1/3) = 15(1/15k + 3/15)
9k  15k  5 = k + 3
6k  5 = k + 3
7k = 8
k = 8/7